2023
DOI: 10.1161/circulationaha.123.063901
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban for Prevention of Thrombotic Events, Hospitalization, and Death in Outpatients With COVID-19: A Randomized Clinical Trial

Abstract: Background: COVID-19 (coronavirus disease 2019) is associated with heightened risks of venous and arterial thrombosis and hospitalization due to respiratory failure. To assess whether prophylactic anticoagulation can safely reduce the frequency of venous and arterial thrombosis, hospitalization, and death in nonhospitalized patients with symptomatic COVID-19 and at least one thrombosis risk factor, we conducted the PREVENT-HD double-blind, placebo-controlled randomized trial (A Study of Rivaroxaban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Moreover, three studies investigated the use of additional antiplatelet therapy, primarily P2Y12 agonists, with one study also including aspirin in the treatment. Furthermore, three studies 19 , 39 , 41 explored postdischarge prophylaxis and four studies 15 , 16 , 18 , 40 explored prophylactic anticoagulation for outpatients, with one study 18 using LMWH (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, three studies investigated the use of additional antiplatelet therapy, primarily P2Y12 agonists, with one study also including aspirin in the treatment. Furthermore, three studies 19 , 39 , 41 explored postdischarge prophylaxis and four studies 15 , 16 , 18 , 40 explored prophylactic anticoagulation for outpatients, with one study 18 using LMWH (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 32 , 39 had some concerns about the selection of the reported results because they did not report major bleeding or mortality. Only six studies 11 , 16 , 19 , 29 , 30 , 40 were assessed as low risk across all domains. Efigure2 (Supplemental Digital Content 3, http://links.lww.com/JS9/C277 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Direct oral anticoagulants can be the choice, but their effectiveness has not been confirmed. 91 Antithrombin and activated protein C are the physiological anticoagulants that are utilized for the treatment of thromboinflammation in sepsis, 92 since not only anticoagulation but endothelial restoration is expected using these agents, and beneficial effects could be expected in select cases 93 ( Fig. 4 ).…”
Section: Anticoagulant and Antiplatelet Therapy For Pascmentioning
confidence: 99%
“…1 2 Several randomized trials have been conducted to assess the role of antithrombotic prophylaxis to reduce the risk of hospitalization, death, and thrombotic events such as venous thromboembolism (VTE), myocardial infarction (MI), and ischemic stroke in those who did not require hospitalization at the time of COVID-19 diagnosis, termed “prehospital” patients. 3 4 5 6 7 8 9 10 All the trials were stopped ahead of plan due to recruitment challenges, lower than expected clinical event rates or futility, leading to inconclusive results.…”
Section: Introductionmentioning
confidence: 99%